Motivation as Myth or Reality in Modern Corporate World in Nepal: A Survey - Nepali, Tej Narayan Prasad (NCC Journal, 2018)
Today’s business organisation is not as before. Big machines, new technology, cut throat completion, changing interest of customers all these has changed the functioning of the corporate management. The modern corporate world want employees to be motivated at their job because most satisfied individuals work at the upper limit of their capacity for the good of the organization, while most dissatisfied individuals pursue ways to increase their level of satisfaction by working for their own gain. Every management tries to coordinate various factor of production in such a way that their contribution is maximum in achieving organizational goals. But, to improve the overall performance in a business it becomes essential to increase the efficiency of human beings. If a person does not have the capability or ability to do a work then he cannot increase his efficiency. On the other hand; even if a person has got the ability but is not properly motivated even then his performance will be low. Hence, the motivation should never be underrated. The organizations of modern corporate world are basically concentrated on achievement of organizational target or goal. In this regard they mostly emphasized to change the traditional approaches of human resource management to motivated employees at work. The different policies regarding wage or salary, promotion, transfer, career development opportunity, job security, social security, bonus, performance appraisal, job evaluation, disciplinary action, etc. have been changed by the organizations of the modern corporate world in such a manner so that the employees could be self-motivated at work. This research paper aims to find out the different factors influencing the level of motivation in modern corporate world and the required changes in the schemes or benefits, policies, etc. for improvement of the level of motivation to minimization of the migration of labour force. The will focus attention to find out that in modern corporate world the motivation is Myth or Reality. NCC Journal Vol. 3, No. 1, 2018, page: 185-199